REFORMASI ADMINISTRASI MELALUI STRATEGI REDISTRIBUSI PEGAWAI DALAM JABATAN FUNGSIONAL TENAGA KESEHATAN DAN GURU DI KABUPATEN SUMEDANG - Wiryanto, Wisber (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Administrative reform was undertaken to address the problem of Indonesia's national development burden, caused by the uneven distribution of Civil Servants (PNS). They accumulate in the West; while in the Central or Eastern regions there is a shortage. Therefore, conducted research in Sumedang regency  in the second half of 2018, with the formulation of the problem how the distribution of civil servants in the functional position of health personnel and teachers in Sumedang regency? The purpose of the study was to formulate  the redistribution strategy in the regions. The study used qualitative descriptive method. Data collection is done through literature study. The result of data analysis shows the distribution of civil servant  in general the excess of employees, but in the functional position of health personnel and teachers in the study area is categorized less. Therefore, the region needs to undertake a civil servant redistribution strategy as an area of excessive civil servants and develop civil servant planning with a negative growth approach.